DELAY IN THE DIAGNOSIS AND PROGNOSIS OF CAECAL CARCINOMA - A STUDY OF 20 CASES - AMIN, MUHAMMAD AMJAD; KHAN, MUHAMMAD AZIM; AYUB, MUHAMMAD; MAHMOUD, MUJAHID; MAHMOUD, MUJAHID; ASHRAF, MUJAHID; CHOUDHRY, ABDUL RASHID (Journal of Ayub Medical College Abbottabad, 2001)
Background: Caecum is the dilated part of the right colon situated in the right iliac fossa, therefore the etiology of this cancer is similar to those of the rest of the colon. Caecal carcinoma is more common in developed countries but it is not a rare disease in underdeveloped countries. This is more common in high socio-economic people who use less fibrous and purified diet. With improvement in health education and social status of the people of Pakistan, there is an emerging trend of Westernization in our society. This may increase the incidence of cancer in Pakistan. Carcinoma of caecum is curable disease if diagnosed early and treated. If we are aware of the pathogenesis, etiology, clinical presentation and management of the disease, we can offer a lot to these patients by diagnosing the caecal carcinoma at an earlier stage, this was the aim of this study. Methods: 20 cases (15 males and 5 females) of Carcinoma of Caecum were studied from January 1997 to December 1999. Out of these six patients presented in emergency ward, 2 as acute appendicitis and 4 as intestinal obstructions. After routine non-specific investigations, our specific investigations included USG abdomen, barium contrast studies and colonoscopy, Barium study and USG remained of primary importance. Results: Most of the patients were between age 45-65 years, oldest patient being 80 years old and the youngest was of only 30 years. Most of the patients presented as mass in the right iliac fossa and only some patients as intestinal obstruction. Right hemicolectomy with primary ileo-transverse anastomosis was our standard surgical procedure and was done in about 14 cases. But in some cases ileo-transverse by-pass operation was done as the growth was locally advanced. However, only the omental biopsy was taken in the cases where carcinoma was too advanced. Conclusions: We think that our sociodemographic factors put a hindrance in detection of this carcinoma at early stages and therefore curative procedures are difficult to bear good results.